Establishment of an orthotopic syngeneic rat model of hepatocellular carcinoma and its validation with microPET-CT imaging. Issue 6 (December 2020) - Singh, Geetanjali; Bendale, Kiran; Talwelkar, Sarang; Pawade, Shital; Gera, Poonam; Patil, Asawari; Chavan, Preeti; Subramanian, Suresh; Chaudhari, Pradip
No abstract available